Влияние усилия замыкания разрывных контактов на переходное сопротивление - Волкова, О.Г. (Електротехніка і електромеханіка, 2011)
Results of research into influence of normal and tangential components of interrupting electric contact closure force on transient resistance are presented. It is shown that the tangential component results in increasing the actual contact area and decreasing the transient resistance.